Child custody; rights of non-muslim and muslim parents in cases of conversion to Islam / Saniah Abd Rahim, Mohamed Fairudz Mohd Hanif and Zubaidah Sharkawi - Abd Rahim, Saniah; Mohd Hanif, Mohamed Fairudz; Sharkawi, Zubaidah (2006)
In Malaysia, both the mother and father have equal chance to apply the guardianship of the child as long as the welfare of the child is well secured. In the battle for child custody when one parent converts to Islam there is conflict of personal laws between the Muslim and non-Muslim spouse. As a general rule under the Syariah law, the mother shall be of all people is the best entitled to the custody of her infant children.1 However if the court is in the opinion that the mother is disqualified under the Hukum Syara and one of the reason is because the mother is a non-Muslim, the right to the custody of the child shall pass to the Muslim father.2 However, this is not the position under the civil perspective in Malaysia under the LRA. What leads us to do this research are to see how does the Civil court and the Syariah court deals with this matter fairly and justly and which decisions will prevail. We also wanted to discover what are the considerations of the both jurisdictions in determining the right of child custody and whether religion is an issue that should be consider by the courts.